Cystic masses of the lateral neck – Proposition of an algorithm for increased treatment efficiency. Issue 9 (September 2018) - Koch, Eva-Maria; Fazel, Asita; Hoffmann, Markus
Abstract: Preoperative discrimination of solitary cervical branchial cleft cysts from cystic lymph node metastasis often is challenging. Surgical excision of the cystic formation and consecutive histopathological examination of tissue specimens are the only means resulting in the correct diagnosis. However, in case of malignancies surgery on the lateral neck prior to the definitive treatment is considered to negatively influence the patients' outcome. The rate of cystic lymph node metastasis in patients presenting with a lateral branchial cleft cyst, localization of the primary tumour and oncological outcome were investigated. Retrospective chart review of 131 patients presenting clinically with solitary lateral cervical cysts between. A malignant tumour was detected in 12 patients (9.2%). Malignant tumours were significantly more frequent in patients older than 40 years of age (22.0%; p = 0.0001). In patients older than 40 years of age with solitary lateral cervical cysts a malignancy should be presumed.